Stability Analysis of State Delay Multiagent Systems with Observer-Based Control Protocols. (4th January 2023) - Li, Xingmei; Deng, Shasha; Wang, Yanhong; Deng, Hongyong
Abstract : The consistency problem of multiagent systems with the output feedback and state delay was considered in this paper. First, the reduced-order observer based on the consensus protocol of state delay is designed, and the consensus protocol is proposed by the output information of neighboring agents. Then, by constructing the Lyapunov–Krasovskii functional and combining matrix inequality and the Schur complement lemma, the asymptotic stability of the system can be obtained, and the consistency of state-delay multiagent systems is derived. Finally, the theoretical results are verified by a simulation example.